The reality of using the educational bag at Central Technical University (Journal of the College of Basic Education, 2022)
In order to find out the reality of the use of educational bags in the Central Technical University, this research was prepared. A questionnaire was developed for this purpose and distributed to 82 teachers in 9 of the university’s institutes and colleges, which included a set of questions about the extent of conviction in the educational bag, the extent of its application, the level of knowledge about it, and the obstacles that they believe prevent its application as a teaching method of self-learning methods. The research also included standing on the role of The participation of teachers in training activities about the educational bag with their opinions about it.